Pengkajian Gaya Busana Tari Jaipongan Karya Sang Maestro - Muhamad Caesar Jumantri; Trianti Nugraheni (Universitas Negeri Medan, 2020)
This study discusses the form of jaipongan dance costume which aims to obtain data from the form of jaipongan dance costume and the characteristics of each style of the jaipongan costume based on the themes. This study uses descriptive analysis method, where the researcher can describe and elaborate the findings with the existing literature. In this research, there are three categories of jaipongan costume work by Gugum Gumbira which are distinguished through the theme of the created dance. From the different themes, it can be concluded that the jaipongan dance work by Gugum Gumbira has its own characteristics from the choice of costume colours to the forms of the costume that are comfortable to wear. Also, the costume prioritizes the essence of the jaipongan dance movement.